Infectious Diseases in Internationally Adopted Children and Intercountry Discrepancies Among Screening Protocols, A Narrative Review - Chiappini, Elena; Bortone, Barbara; Borgi, Sara; Sollai, Sara; Matucci, Tommaso; Galli, Luisa; de Martino, Maurizio (Frontiers in Pediatrics, 2019)
Internationally adopted children (IAC) require thorough health assessments at time of arrival in host countries. Being at higher risk for infectious diseases as gastrointestinal parasites, tuberculosis, hepatitis, congenital syphilis and Human immunodeficiency virus, an early diagnosis of infectious diseases is fundamental for the optimal management of the child, and, also, to reduce the risk of transmission to the adopting community. Comparative analysis of screening protocols adopted in Europe, United States, Canada disclosed different approaches to the adopted children. A homogeneous and internationally shared standard of care in the management of IAC should be provided.